Transcriptional regulation of KCNA2 coding Kv1.2 by EWS::FLI1: involvement in controlling the YAP/Hippo signalling pathway and cell proliferation - Maryne Dupuy; Anaïs Postec; Mathilde Mullard; Aurélie Chantôme; Philippe Hulin; Régis Brion; Maxime Gueguinou; Laura Regnier; Marie Potier-Cartereau; Bénédicte Brounais-Le Royer; Marc Baud’huin; Steven Georges; et al. (Cell Communication and Signaling)
Abstract Background Ewing sarcoma (ES), the second main pediatric bone sarcoma, is characterised by a chromosomal translocation leading to the formation of fusion proteins like EWS::FLI1. While several studies have shown that potassium channels drive the development of many tumours, limited data exist on ES. This work therefore aimed to study the transcriptional regulation of KCNA2 and define the involvement of the Kv1.2 channel encoded by KCNA2 in a key function of ES development, cell proliferation. Methods KCNA2 expression in patients and cell lines was measured via bioinformatic analysis (RNA-Seq). The presence of a functional Kv1.2 channel was shown using patch-clamp experiments. Molecular biology approaches were used after EWS::FLI1 silencing to study the transcriptional regulation of KCNA2. Proliferation and cell count assessment were performed using cell biology approaches. KCNA2 silencing (siRNA) and RNA-Seq were performed to identify the signalling pathways involved in the ability of KCNA2 to drive cell proliferation. The regulation of the Hippo signalling pathway by KCNA2 was studied by measuring Hippo/YAP target genes expression, while YAP protein expression was studied with Western-Blot and immunofluorescence approaches. Results This research identified KCNA2 (encoding for a functional Kv1.2 channel) as highly expressed in ES biopsies and cell lines. The results indicated a correlation between KCNA2 expression and patient survival. The data also demonstrated that KCNA2/Kv1.2 is a direct target of EWS::FLI1, and identified the molecular mechanisms by which this chimeric protein regulates KCNA2 gene expression at the transcriptional level. Furthermore, the results indicated that KCNA2 expression and Kv1.2 activity regulate ES cell proliferation and that KCNA2 expression drives the Hippo/YAP signalling pathway. Using the specific Kv1.2 channel inhibitor (κ-Conotoxin), the results suggested that two complementary mechanisms are involved in this process, both dependently and independently of Kv1.2 functional channels at the plasma membrane. Conclusion This study is the first to describe the involvement of KCNA2 expression and Kv1.2 channel in cancer development. The study also unveiled the involvement of KCNA2 in the regulation of the Hippo/YAP signalling cascade. Thus, this work suggests that KCNA2/Kv1.2 could be a potential therapeutic target in ES.